Liver Cirrhosis Update and Current Challenges - Tsoulfas, Georgios (IntechOpen, 2017)
Liver cirrhosis represents one of the major challenges for most physicians and surgeons on a global scale. This book provides practicing hepatologists, gastroenterologists and liver surgeons with a valuable tool in their efforts to understand the (molecular) mechanisms involved, be updated regarding the newest and less invasive diagnostic methods, and educate themselves about the challenges involved in the management of liver cirrhosis and its complications. The authors of this book represent a team of true global experts on the topic. In addition to the knowledge shared, the authors provide their personal clinical experience on a variety of different aspects of liver cirrhosis, giving us a well-rounded overview.